Seaweed and melatonin in the induction of tolerance to recurrent water deficit in papaya - Rangel Ferreira, Thayanne; Tognere Polonini, Giuseppe; Freitas Fonseca, Letícia; Tatagiba Franco Brandão, Cristhiane; Ralph Falqueto, Antelmo; Romais Schmildt, Edilson; de Souza Oliveira, Vinicius; de Oliveira Arantes, Lúcio; Nascimento de Santana, Enilton; Dousseau-Arantes, Sara (Frontiers in Plant Science, 2025)
IntroductionAbiotic stresses cause physiological and biochemical imbalances, such as stomatal closure, reduced photosynthesis, and changes in water balance, biomass allocation, and carbohydrate metabolism, compromising growth and, consequently, productivity. One strategy to minimize the effects of these stresses in agriculture is the use of biostimulants. Therefore, the objective of this study was to evaluate the effects of foliar applications of melatonin, Ascophyllum nodosum, and Lithothamnium calcareum on papaya plants subjected to three recurring cycles of water deficit on physiological performance, carbohydrate allocation, and vegetative growth.MethodsThree water deficit and recovery trials were conducted on ‘Aliança’ papaya seedlings. Before imposing the water deficit, solutions of the biological regulator melatonin and seaweed extracts from A. nodosum and L. calcareum were applied via foliar application. Water potential, chlorophyll a fluorescence, photosynthetic pigments and vegetative growth of seedlings were evaluated.ResultsSeaweed and melatonin promoted increased water retention by decreasing leaf water potential and maintaining and restoring photosynthetic functions. In the second cycle of water deficit, there were significant reductions in maximum photochemical quantum yield and an increase in the energy flux dissipated per reaction center. Seaweed and melatonin also reduced total soluble sugar levels. Melatonin also promoted increased growth in specific stem length and specific root length.DiscussionFoliar applications of melatonin, A. nodosum, and L. calcareum proved effective in mitigating the effects of water deficit in papaya seedlings. Chlorophyll a fluorescence indicated that photosynthetic functionality was most affected during the second drought cycle, with inhibition of the photosynthetic apparatus during this period. Water stress reduced chlorophyll levels, possibly as a strategy to minimize photooxidative damage. Among the biostimulants tested, melatonin stood out in terms of specific stem length and specific root length growth, indicating greater adaptation to water deficit.